2014
DOI: 10.1140/epjc/s10052-014-3067-0
|View full text |Cite
|
Sign up to set email alerts
|

Thin-shell wormholes supported by total normal matter

Abstract: The Zipoy-Voorhees-Weyl (ZVW) spacetime characterized by mass (M) and oblateness (δ) is proposed in the construction of viable thin-shell wormholes (TSWs). A departure from spherical/cylindrical symmetry yields a positive total energy in spite of the fact that the local energy density may take negative values. We show that oblateness of the bumpy sources/black holes can be incorporated as a new degree of freedom that may play a role in the resolution of the exotic matter problem in TSWs. A small velocity pertu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…Finally, we admit that in each case our energy density happens to be negative so that we are confronted with exotic matter. In a separate study we have shown that not to have exotic matter to thread the wormhole we have to abandon spherical symmetry and consider prolate/oblate spheroidal sources [48].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we admit that in each case our energy density happens to be negative so that we are confronted with exotic matter. In a separate study we have shown that not to have exotic matter to thread the wormhole we have to abandon spherical symmetry and consider prolate/oblate spheroidal sources [48].…”
Section: Resultsmentioning
confidence: 99%
“…Different TSW solutions have been proposed, including, charged TSW [8,9], TSW in heterotic string theory [10], TSW from a noncommutative BTZ black hole [11], TSW in Einstein-Maxwell-Gauss-Bonnet gravity [12], rotating TSW [13,14], TSW from scalar hair black hole [15], TSW supported by normal matter [16,17], cylindrical TSW [18][19][20][21][22][23][24], and TSW with a cosmological constant [25,26], and wormholes in the framework of mimetic gravity; see [27] and the references therein. Recently, Das [28], showed that by replacing the classical trajectories (geodesics) with the so-called quantal or Bohmian trajectories gives rise to the quantum version of the Raychaudhuri equation (QRE).…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this work we provide thin-shell wormholes from noncommutative BTZ black hole in (2+1)-dimensional gravity. A well studied of thin-shell wormholes in lower dimensional gravity have been found in [67][68][69][70][71].…”
Section: Introductionmentioning
confidence: 99%